Clima Seco e Formação de Dunas Eólicas durante o Holoceno Médio em Taquaruçu, Mato Grosso do Sul - PAROLIN, MAURO; STEVAUX, JOSÉ CÂNDIDO (Pesquisas em Geociências, 2001)
Holocene sandy deposits interpreted as of eolian origin were studied at Taquaruçu, MS (22º30’ S / 53º20’ W). That area is constituted of hills with 5 to 12 m of height over the regional surface, with lightly asymmetric profile, which, morphologically remind eolian dunes quite dissipated, covered by scattered shrub-arboreal vegetation. The deposits are mainly composed of fine to very fine (35 and 54%), medium quartzose sand (7%), with rare granules in the basal interval and clay (4%). Sediment is almost totally massive, probably, by intensive root bioturbation. Structures generated by dissipation and fluidization were also identified. The studied profiles are very similar and presented a temporal hiatus between 3,3 and 3,7 ka BP. The curve of magnetic susceptibility also displays a coincident inflection with the identified discontinuity in the age curve. It was possible to conclude that the area was submitted to a drier climate than the current during the Middle Holocene. Under this climate there was reduction in the vegetable covering and the consequent mobilization of the sand generating an erosive surface and the formation of small dune field. This dry period at the end of Middle Holocene is also identified in other localities such as in SE and Central area of Brazil, and in NE of Argentina. However, this is the first time that eolian processes of such intensity were described in the studied area, and a revision in the definition of aridity intensity of the short dry period of the Holocene is suggested.